A novel hierarchical ZnO-nanosheet-nanorod-structured film for quantum-dot-sensitized solar cells. (1st June 2018) - Cai, Junhao; Chen, Zeng; Li, Shengjun; Dong, Shaokang; Wei, Chaochao; Li, Fumin; Peng, Yaru; Jia, Xiyang; Zhang, Weifeng
Abstract: This study reported the fabrication of hierarchical ZnO NS-NR-structured films by the assembly of ZnO NRs (NRs) on ZnO nanosheets (NSs) by a hydrothermal method. The morphology of the as-prepared ZnO NS-NR films was affected by several factors, such as the TiO2 intermediate layer, the concentration of Zn(CH3 COO)2 in the seed precursor solution, and the hydrothermal reaction time. ZnO NRs were vertically grown on the ZnO NSs under specific conditions. Such ZnO NS-NR films exhibited considerably higher light-scattering ability compared with that of the ZnO NS films. Quantum dot (QD)-sensitized solar cells were assembled using the CdS/CdSe QDs co-sensitized ZnO NS-NR films as the photoanodes. The growth of the ZnO NRs led to the improvement in the short-circuit current density from 12.4 mA cm −2 to 15.1 mA cm −2 . A high power conversion efficiency of 6.0% was obtained with (NH4 )2 TiF6 treatment for 4 min.